2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6945051
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perceiving color in living environment on QEEG, Oxygen saturation, pulse rate, and emotion regulation in humans

Abstract: Light and color have been shown to have substantial physical, psychological and sociological effects on humans. Hence, an investigation on the effect of changes in light and color to the biological signals is a challenging problem. Five participants were measured the oxygen saturation (SpO2), pulse rate, and quantitative electroencephalogram (QEEG) in six colors (white, blue, green, yellow, red and black) of living environment for 5 minutes per color. Then all participants were asked to answer the emotional qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Also, it is believed that preferred colours have a guiding effect on individuals [16]. Red, blue and green objects showed different effects on the brain activity [4]. It was reported that age has an important effect on colour preferences and also that colour preferences change with age and maturity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, it is believed that preferred colours have a guiding effect on individuals [16]. Red, blue and green objects showed different effects on the brain activity [4]. It was reported that age has an important effect on colour preferences and also that colour preferences change with age and maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Each colour has different variances [2,4]. In nature, there are three primary colours: red, yellow and blue.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 3 more Smart Citations